A young student vaccines bilateral relations and psychological characteristics of primary school age - Hoshimova Dilorom Anvarovna (International Journal on Orange Technologies, 2021)
The article focuses on issues such as the full development of brain structure and neural mental processes in children for school, the development of visual motor coordination and fine motor skills, high productivity of logical thinking